new beginnings : postwar British art from the collection of Ken Powell - Grieve, Alastair; Scottish National Gallery of Modern Art, Edinburgh (Edinburgh : Trustees of the National Galleries of Scotland, 1992)
Adams, Robert ; Armitage, Kenneth ; Ayres, Gillian ; Barns-Graham, Wilhelmina ; Butler, Reg ; Clough, Prunella ; Ernest, John ; Frost, Terry ; Gilbert, Stephen ; etc.
new beginnings : postwar British art from the collection of Ken Powell, Scottish National Gallery of Modern Art, Edinburgh, 13 November 1992 - 3 January 1993
boek